(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
Climate change is causing strong internal migration, and by 2050, 216 million people living in six regions of the world are expected to be forced to leave the area where they live and move to other areas. In particular, the number of environmental migrants is predicted to be 86 million in sub-Saharan Africa, 49 million in East Asia and the Pacific, 40 million in South Asia, 19 million in North Africa, and 17 million in Latin America after 27 years1. Among these regions, Central Asia and more than 5 million people living there prove that this problem is very urgent for the countries of the region